Hubungan Status Gizi Dengan Kejadian Infeksi Respiratorik Akut (IRA) Bagian Bawah ada Anak Usia 1-5 Tahun Di RSUD Sukoharjo - Arisanti, Sandhya Putri, dr. Shinta Riana Setiawati, Sp.A, M.Kes, dr. Devi Usdiana Rosyidah, M.Sc (2015)
Background : Acute Lower Respiratory Tract Infection (ALRTI) is ainfections caused by viruses, bacteria, or trauma that occurred from the larynx down and divided into croup (epiglotitis and laringo-tracheo-bronchitis), bronchitis, bronchiolitis, and pneumonia. ALRTI vulnerable population is children aged under five years old who have health problems such as malnutrition Objectives : To determine the relationship between nutritional status and the incidence of ALRTI in children aged 1-5 years in Sukoharjo Hospital. Methods : This study uses an analytical observational cross-sectional approach, the subjects in this study were children aged 1-5 years were enrolled in the treatment and hospital medical record Sukoharjo in January 2015. The technique used is the consecutive sampling. The whole subject is 84 children, consisted of 42 children with malnutrition and 42 children with good nutrition. The data obtained are presented in tables and analyzed using Chi Square test with SPSS 17.0 for Windows. Results : From the Chi square test p value of 0.001 obtained, it can be stated H0and H1 accepted. There is a significant association between nutritional status and the incidence of ALRTI. Additionally obtained value OR = 5.5, which means malnutrition increases the risk by 5,5 times lower compared to the ALRTI with good nutrition. Conclusion : There is a relationship between the nutritional status and the incident of ALRTI.